Responses of soil heterotrophic respiration and microbial biomass to organic and conventional production systems - Dhakal, Kripa; Parajuli, Madhav; Jian, Siyang; Li, Jianwei; Nandwani, Dilip (Frontiers in Soil Science, 2022)
The objective of this study is to determine soil heterotrophic respiration and microbial biomass carbon in organic and conventional production systems. The field experiment was conducted from March to May 2019 at the Tennessee State University research farm. Leafy green vegetables were grown in conventional production system in an open field, and they were grown in an organic production system, using three different row covers (agribon cloth, insect net, and plastic) and in open field. Soil samples (0-15cm) were collected from the two production systems. Heterotrophic soil respiration rate (Rs), microbial biomass carbon (MBC), and biomass-specific heterotrophic respiration rate (Rss; the inverse of Rss is used as a proxy for microbial carbon use efficiency) were quantified. The results showed heterotrophic soil respiration (Rs) and biomass-specific respiration (Rss) were higher in the conventional production system but the organic production system significantly enhanced MBC relative to the conventional production system. Our results suggest that the organic production system not only promoted soil microbial abundance but also limited soil heterotrophic respiration to the atmosphere governed by the elevated carbon use efficiency.